Efektifitas Konseling Kelompok Berbasis Karakter Masyarakat Banyumas dalam Meningkatkan Sikap Asertif - Alief Budiyono (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
This article discusses the group counseling effectiveness based on Banyumas society character to improve the university students’ assertive attitude. Camblaka and semblothongan are the special characteristics of Banyumas society commonly. The research is conducted using Wilcoxon analysis to compare the pre-test and post-test result, with the assertive attitude analysis of Guidance and Counseling students of IAIN Purwokerto. Assertive communication has an important role for social adaptation. If an individual communicates assertively, so he could state his feeling and belief openly, directly, honestly, and in the appropriate manner to improve him to be more self confident, well-mannered, friendly, and to socialize better so he could have good social adaptation. The result of the study shows that the group counseling service is effective to improve students’ assertive attitude, proven by the calculating result of students’ assertive attitude before and after getting the group counseling service get the improvement 15.59% from 52.21% becomes 67.80%, it means that the difference of 15.59% is significant to the belief as 95%. So, the Banyumasan society characters, especially camblaka and semblothongan could be an alternative method of effective group counseling to build closeness between counselor and clients to build clients’ assertive attitude.